ON INTEGRAL OPERATORS OF BERGMAN TYPE ON THE UNIT BALL OF ${\mathbb R}^n$ - Tonoyan, Ye.G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
We prove the boundedness of Bergman type integral operators in mixed norm spaces over the unit ball of ${\mathbb R}^n$. Bounded harmonic projections are found in the mixed norm and Lipschitz spaces. Corresponding Forelli–Rudin type theorems are proved.
Keywords: unit ball in $\mathbbR^n, harmonic function, mixed norm space, Bergman space, Bergman operator, projection, Lipschitz space